The effectiveness of emotion-oriented couple therapy on empathy, internal coherence and sexual satisfaction of women with marital conflicts in Isfahan - Khosh Akhlagh, Hassan; Nahavandi, Melika (Psychology of Woman Journal, 2022)
This research aimed to investigate the effectiveness of emotional couple therapy on empathy, internal cohesion, and sexual satisfaction of women with marital conflicts in Isfahan. The experimental research method was pre-test, post-test with a control group, and a 2-month follow-up phase. The statistical population was all married women with marital conflicts who were referred to counseling centers and psychological services in Isfahan city in 2022. In the first stage, 30 people who scored higher than 108 on the scale of marital conflicts were selected using the available sampling method. Then they were replaced by a simple random method in an experimental group (15 people) and a control group (15 people). The first experimental group underwent ten 90-minute emotion-oriented couple therapy interventions adapted from Johnson (2008). However, the control group did not receive any intervention and remained on the waiting list. The Kansas Marital Conflict Scale (KMCS) by Eggman et al. (1985), the Empathy Scale (ES) by Davis (1983), the Internal Consistency Questionnaire (SOC) by Antonovsky (1993) and the Sexual Satisfaction Questionnaire (ISS) by Hudson et al. (1981) was used to collect data. The analysis of the information obtained from the implementation of the questionnaires was carried out through SPSS software version 24 in two descriptive and inferential sections (mixed variance analysis and Bonferroni's post hoc test). The results showed that the said treatment significantly affected empathy, internal cohesion, and sexual satisfaction of women with marital conflicts in the post-test and follow-up phase compared to the control group (P